Seed desiccation tolerance and germination of four Puya (Bromeliaceae) high-andean tropical species from Colombia - Manuela Calderón-Hernández; Laura Victoria Pérez-Martínez (Caldasia)
Ex-situ seed conservation is one of the most effective tools for biodiversity and genetic diversity protection. In the context of global climate change, ex situ conservation has become an important strategy that must be strengthen and integrated with in situ conservation strategies. The main objective of this study was to document the desiccation tolerance and germination properties of four species from Puya and provide tools that allow the ex situ conservation of this and other closely related species. These species are distributed in Páramo, a threatened ecosystem despite of its value as a water reservoir and supplier for urban population. Seed morphological variables and moisture content (MC) were measured before a test of germination was conducted with three different moisture contents (fresh seeds, 10–12 % and 3–5 %). Germination percentage and the mean germination time were evaluated. The germination was above 80 % in all the species with no significant differences when decreasing MC. There were no significant differences in mean germination time. Seed viability for the four species was high, as compared to other Páramo species. The results indicate that all species are orthodox. Therefore, this genus has great potential to be conserved in seed banks, which will contribute to diversity conservation of native species from tropical Andean highlands, and can be implemented in germination protocols for their propagation and reintroduction in restoration programs.